THE EFFECT OF DIRECT AND INDIRECT COMPENSATION TO EMPLOYEE’S LOYALTY (Case Study at Directorate of Human Resources in PT. Pos Indonesia (Persero) Jalan Cilaki No. 73 Bandung) - Manurung, Siska Purnama; Kasenda, Regina Keren (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2017)
As company’s main resource, the employees welfare need to be assured, such as through compensation. A proper compensation will make the employees loyal to the company and increase their contribution and productivity.The phenomenon that occurs is the high turnover rate of state-owned company or government-owned company caused by the low level of compensation. PT. Pos Indonesia (Persero) is a state-owned company engaged in courier, logistics, and financial transactions in Indonesia.This research was conducted in Direktorat SDM PT. Pos Indonesia (Persero) Jalan Cilaki No. 73 Bandung to assess the influence of compensation, both directly and indirectly, to the employees’ loyalty. Multiple linear regression analysis indicates that direct compensation has 38, 8% significant and positive relation with the employee’s loyalty, while indirect compensation has 48, 2% significant and positive relation with the employee’s loyalty.